Consolidated Financial Statements of Enterprises of Oil and Gas Complex: Composition, Elements and Rules of Consolidation - Кафка, С. М.; Хома, С. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
Global trends determine the strengthening of the business association of enterprises, mergers and acquisitions to achieve its goals. However, it faces new challenges to the systems of accounting and reporting in the following processes for strengthening information requirements of the business is increasingly more important, allows both affect the movement of capital within the group companies and to attract additional financial resources from other contractors.